PENCEMARAN LINGKUNGAN PADA TUNGKU PEMBUATAN BRIKET KOKAS DAN PENGECORAN LOGAM SERTA PENCEMARAN LOGAM BERAT DI SENTRA INDUSTRI KECIL - Hasnedi, Hasnedi (Jurnal Energi dan Lingkungan (Enerlink), 2011)
The coke production process by baking semi-coke briquette in a coke’s bakingoven will produce flue gas and smoke. The same also happens in its utilizationtest in metal foundry kiln known as “tungkik” (plunging) smelting kiln. The gasand smoke predictably contain heavy metals and polluted chemical compoundsthat will pollute the environment and disturbing the health of workers if theirconcentrations pass over defined standard quality level. The objective of thisstudy is to examine the amount of heavy metals and chemical compoundpollutants produced in the process of baking semi-coke to produce coke and inthe utilization of coke as fuel in tungkik kilns. Measurement results show thatheavy metals in the kiln’s chimneys and chambers such as As, Cd, Pb, and Hgcould not actually be detected, while Fe, Na, Al, Ca, and K could be easilydetected. The concentrations of such metals are in the range of: Na = 100-315µg/m3, Al = 215-360 µg/m3, Ca = 786-1330 µg/m3, Fe = 478-2300 µg/m3, and K = 0.25-0.5 µg/m3. Meanwhile pollutants from other chemical compounds in the flue gas are NO2 = 80.7785-83.3725 mg/m3 and SO2 = 10.85-10.98 mg/m3. Pollutantsfrom ambient air are NO2 = 179.11-236.49 µg/Nm3, SO2 = 112.56-256.52 µg/Nm3,CO = 43.80-100.98 µg/Nm3, HC = 0.05-0.64 µg/Nm3, and O3 = 2.8098-19.6065µg/Nm3. The total particle’s content is also low, which is about 0.283 mg/m3 in thecoke baking oven’s chimneys, 0.554 mg/m3 in the tungkik kiln’s chimneys and0.259 mg/m3 in the metal melting locations. Comparison of the measurementresults with that of quality standard defined by the government regulation of theRepublic of Indonesia No.41 Year 1999 about air pollution control, show that theresults is far below the tolerated level. Therefore, the existence of coke bakingoven is still feasible and safe to the environment.Kata kunci: briket kokas, pencemaran lingkungan, logam berat